Exclusive breastfeeding behavior among mothers aged - Sari, Anur Rahima; Meilani, Niken; Maryani, Tri (Jurnal Kesehatan Ibu dan Anak, 2019)
The number of adolescent pregnancies in Indonesia was still high. This study aimed to find out the exclusive breastfeeding behavior among mothers aged <20 years old. This study was a quantitative used cross-sectional approach. The sample in this study was mothers aged <20 years who had babies aged 6-24 months in Karangmojo, Semanu, Semin, Gunung Kidul Regency in 2019. Minimal sample calculation by Lemeshow was 45 respondents. Data collected by a structured questionnaire. Data analysis involved univariate, bivariate analysis using the chi-square test and fisher's exact test, while multivariate analysis used logistic regression. The results showed that 75.5% of adolescent mothers aged <20 years old practice exclusive breastfeeding. Bivariate analysis showed that occupational factors (p-value = 0.001), parity (p-value = 0.001), pregnancy status (p-value = 0.010), family support (p-value = 0.002) and husband support (p-value = 0.003) were correlated to exclusive breastfeeding. Multivariate analysis showed husband support (p-value = 0.005; OR = 26.591). Husband support as the most influential factor to exclusive breastfeeding behavior among mothers <20 years old